Ministerial decree no.162 of the year 2019 Regarding the Issue of the Financial and Administrative Regulations for the Employment, Care and Protection of the Irregular Labor (Construction, Agricultural, Seasonal, Temporary Workers and the Like) = قرار وزاري رقم 162 لسنة 2019 بشأن إصدار اللائحة المالية والإدارية لتشغيل ورعاية وحماية العمالة غير النتظمة (عمال المقاولات والزراعة والموسميين والمؤقتين ومن في حكمهم) / Prime Ministry. - Egypt. Prime Ministry. (2025)
Ministerial decree no.162 of the year 2019 Regarding the Issue of the Financial and Administrative Regulations for the Employment, Care and Protection of the Irregular Labor (Construction, Agricultural, Seasonal, Temporary Workers and the Like) – financial and administrative regulations of employment, care and protection or Irregular Labor (Construction, Agricultural, Seasonal, Temporary Workers and the Like) – chapter 1: definitions and general provisions – chapter 2: employment monitoring committees -- chapter 3: departments of the employment and care of Irregular Labor -- chapter 4: follow-up and inspection works -- chapter 5: the financial system اللائحة المالية والإدارية لتشغيل ورعاية وحماية العمالة غير المنتظمة (عمال المقاولات والزراعة والموسميين والمؤقتين ومن فى حكمهم) – الفصل الأول التعاريف والأحكام العامة – الفصل الثانى لجان متابعة التشغيل – الفصل الثالث إدارات تشغيل ورعاية العمالة غير المنتظمة – الفصل الرابع أعمال المتابعة والتفتيش – الفصل الخامس النظام المالى